Utilization of Disposable Mask Waste and Coconut Fiber as an Acoustic Composite Material - Khairunnissa Ramadhani; Arrizal Abdul Aziz; Miftahul Akbar Ramadhan; Amara Huaida Alifah; Try Ramadhan (DIMENSI (Journal of Architecture and Built Environment), 2024)
This research aims to utilize disposable mask waste and coconut fiber as an acoustic composite material and identify its sound absorption characteristics. The method used in this research is an experiment to produce four samples with different non-woven polypropylene and coconut fiber composition. The samples went through multiple tests to identify its morphology, mass change in different temperatures, density, and sound absorption coefficient. The result of this research shows that these materials display sound absorption characteristics and can be applied for acoustic purposes. Acoustic material with 100% non-woven polypropylene displays the best sound absorber characteristics, especially for 500Hz frequency sound. However, acoustic material with composition of 90% non-woven polypropylene and 10% coconut fiber shows a better sound absorption coefficient in 2000Hz frequency.